Electric vehicle routing problem: A systematic review and a new comprehensive model with nonlinear energy recharging and consumption - Xiao, Yiyong; Zhang, Yue; Kaku, Ikou; Kang, Rui; Pan, Xing (Renewable & sustainable energy reviews, 2021)
Electric vehicles (EVs) are witnessing a surge in demand and production for their environmental benefits. This study reviews the development of electric vehicle routing problem (EVRP) in transport logistics. The review found that few existing EVRP models considered integrally the unique characteristics of EVs, such as the nonlinear charging function, nonlinear electricity-consumption function, and dynamic driving ranges. This study develops a new comprehensive model of the EVRP that considers a general energy/electricity consumption function for EVs that factor in energy losses (aerodynamic, tire friction, drivetrain, ancillary, and kinetic/potential losses), nonlinear charging function with the piecewise linearization technique, efficient visits to charge stations, and continuous decision variables for speed, payload, travel time, recharging, etc. The newly developed model is much closer to reality by integrating most of the unique characteristics of EVs known so far, and therefore it advances the state-of-the-art in EVRP. Computational experiments on Solomon's instances were done to exhibit the effectiveness and efficiency of the developed model under the effects of air conditioner, battery capacity, and travel speed. These experiments demonstrated that the model can obtain more practical logistics plans for an EV fleet with a lower total emissions cost and higher energy utilization. •A systematic literature survey of the EVRP is provided.•A general energy consumption function of EVRP is established.•A new comprehensive EVRP model is presented with energy recharging and consumption.•Computational experiments were done to analyze the model characteristics.